Cell Cycle Regulation and Differentiation in Cardiovascular and Neural Systems - Giordano, Antonio.; Galderisi, Umberto. (Springer New York : Imprint: Springer, 2010)
Complex physiopathological relationships have been proven to exist between two of the bodys most vital organs; the brain and the heart. In Cell Cycle Regulation and Differentiation in Cardiovascular and Neural Systems Antonio Giordano, Umberto Galderisi and a panel of the most respected authorities in their field offer an in-depth analysis of the differentiation process in two systems that have profound relationships with one another. The text looks at several aspects of the cardiovascular and nervous systems from a new point of view, describing the differences and similarities in their differentiation pathways with an emphasis on the role of cell cycle regulation and cell differentiation. Topics discussed include neurogenesis in the central nervous system, neural stem cells, and the basic-helix-loop-helix transcription factors in neural differentiation. Ground-breaking and authoritative, Cell Cycle Regulation and Differentiation in Cardiovascular and Neural Systems is a must have for all researchers in cardiovascular medicine and neuroscience and will prompt the scientific community to perceive cell cycle regulation and differentiation under a novel and more comprehensive light.